P-150 Moving towards integrated end of life care in east london. Issue Volume 5: Issue (2015)Supplement 3 (1st November 2015) - Dodds, Nigel; Bradley, Ruth
Abstract : St Joseph's Hospice sits in a well known and loved area of East London. The local population experiences a hospital death rate higher than many other parts of England. In order to improve choice at the end of life, and to transform the delivery of care for the people in the last years of life in East London, St Joseph's Hospice has collaborated with two of its local boroughs to support the development of models of integrated care. Whilst this means closer collaboration with our partners working in the community health teams, our community palliative care team has needed to transform to meet the shifting needs of our populations and community health teams to support patient choice at the end of life. A new model of care best described by Hansford (2013) has been introduced. This has shifted the focus of the team from being 'supportive and advisory', Monday-Friday, 9–5, to a team that has a proactive focus on delivering care, with more attention to being interventionalist, that works alongside our community health team partners, working 7 days a week, 24 h a day. In this presentation, with data collected during this process of change management, we will demonstrate the impact of the new model of care and how this is delivered as part of local approaches to integrated care, through an audit of interventions and outcomes relating to the team's new way of working.